Neurophysiologic and Cognitive Changes Arising from Cognitive Training Interventions in Persons with Mild Cognitive Impairment: A Systematic Review - Eliane C. Miotto; Alana X. Batista; Sharon S. Simon; Benjamin M. Hampstead (Neural Plasticity)
Background. Previous reviews have generally reported cognitive//behavioral improvements after cognitively oriented treatments (COTs) in persons with MCI. However, comparatively little is known about the neural mechanisms associated with such cognitive improvement. Objective. The primary aim of the current review was to examine neurophysiological changes measured by functional magnetic resonance imaging (fMRI) and possible cognitive changes following COTs in those with MCI. Methods. An extensive literature search was conducted up to August 2018. Inclusion criteria were (1) studies that evaluated the effects of the COTs in patients with amnestic single- or multiple-domain MCI using fMRI, (2) the MCI patient sample having met Petersen’s or Jack/Bond’s criteria, (3) randomized and/or controlled trials, (4) fMRI and cognitive assessments completed pre- and post-intervention, and (5) articles available in English. Results. Amongst the 26 articles found, 7 studies were included according to the above inclusion criteria. A total of 3 studies applied rehearsal-based strategies as the primary intervention, all of which used computerized cognitive training. Four studies used fMRI to investigate the neurophysiologic and cognitive changes associated with memory strategy training. The majority of the studies included in this review showed evidence of improved objective cognitive performance associated with COTs, even in tasks similar to everyday life activities. In addition, there were significant changes in brain activation associated with interventions, in both typical and atypical brain areas and networks related to memory. Conclusions. Although additional studies are needed given the small sample size, these initial findings suggest that cognitive improvement after COTs is generally associated with both compensatory (i.e., engaging alternative brain regions or networks not “typically” engaged) and restorative (i.e., reengaging the “typical” brain regions or networks) mechanisms.